Low concentrations of serum testosterone predict acute myocardial infarction in men with type 2 diabetes mellitus - Daka, Bledar (BMC Endocr Disord, 2015)
BACKGROUND: The aim of the present study was to investigate the associations between endogenous testosterone concentrations and the incidence of acute myocardial infarction (AMI) in men and women with and without type 2 diabetes. METHODS: The study comprised 1109 subjects ≥40 years of age (mean age 62 ± 12 years) participating in a baseline survey in Sweden in 1993–94. Information about smoking habits and physical activity was obtained using validated questionnaires. Serum concentrations of testosterone and sex hormone-binding globulin (SHBG) were obtained using radioimmunoassay. Diagnosis of type 2 diabetes was based on WHO’s 1985 criteria. Individual patient information on incident AMI was ascertained by record linkage with national inpatient and mortality registers from baseline through 2011. RESULTS: The prevalence of type 2 diabetes at baseline was 10.0 % in men and 7.5 % in women. During a mean follow-up of 14.1 years (±5.3), there were 74 events of AMI in men and 58 in women. In age-adjusted Cox models, a significant inverse association between concentrations of testosterone and AMI-morbidity was found in men with type 2 diabetes (HR = 0.86 CI (0.75–0.98)). In a final model also including waist-to-hip ratio, systolic blood pressure, total cholesterol and active smoking, the association still remained statistically significant (HR = 0.754 CI (0.61–0.92)). CONCLUSION: Low concentrations of testosterone predicted AMI in men with type 2 diabetes independent of other risk factors. Trials with testosterone investigating the effect regarding cardiovascular outcome are still lacking. Future trials in this field should take into account a modification effect of diabetes.